A CONCEPTUAL ANALYSIS OF FRAUD AND CORRUPTION IN THE PUBLIC SECTOR - Corina BOLOȘ (Annals of the University of Oradea: Economic Science)
This paper explores the connection between corruption and usurpation aspirations. The article demonstrates that corruption continues to permeate all levels of the political and socio-economic system. The study reveals strong evidence that apart from the traditional factor of corruption – it is also a driver for fraud. In short, our analysis draws attention to the fact that the phenomena of corruption and fraud in society are placed at the center of public opinion, daily either through the press, radio or television, from the Parliament's rostrum and other sources, various facts of a criminal nature regarding fraud and corruption in Romanian society in which representatives of state authorities, political parties and officials of various ranks are involved. It is obvious that the appearance and development of these phenomena has destabilized Romania over time. It is also very true that in the analysis and evaluation of these phenomena, sometimes rhetorical notions are used, inaccurate or exaggerated statements are made. However, there are important differences between the phenomena of fraud and corruption in the legal sense and their perception by public opinion.